Feasibility study of linking anonymous data of children in longitudinal school-based prevention research - Vacek, Jaroslav; Gabrhelík, Roman (Adiktologie, 2024)
INTRODUCTION: Longitudinal prevention research in adolescents often involves sensitive data collection, necessitating anonymity. Self-Generated Identification Codes (SGICs) have emerged as a tool for linking anonymous data while preserving privacy, but their effectiveness, especially in large-scale studies, remains underexplored. This study aimed to assess the feasibility of using SGICs for linking anonymous longitudinal data in a school-based substance use prevention study. METHODS: We utilized a three-armed randomized control trial design, utilizing data from the Czech Unplugged Study. The study involved schoolchildren from 71 schools in the Czech Republic, tracked from 6th to 9th grade. SGICs were used to link anonymous survey data across multiple waves. The sample comprised 2,571 pupils, aged 11–13 years, with data collected over seven waves, resulting in a total of 15,289 questionnaires. RESULTS: The study demonstrated a high rate of SGIC completion (99.2%) and substantial linkability across survey waves. However, errors in SGICs were observed, with certain characters being more prone to inaccuracies. The results showed that 8.5% of all children’s SGICs contained one or more missing or erroneous characters; the proportion of errors gradually decreased over time. CONCLUSION: The study’s findings provide insights into the practicality and challenges of using SGICs in large-scale, longitudinal studies. SGICs offer a viable solution for linking longitudinal data while maintaining participant anonymity. The study highlights the importance of careful SGIC design and the need for further research into optimizing this methodology for large-scale adolescent studies.